Computer graphics programming in OpenGL with Java - Gordon, V. Scott; Clevenger, John (Professor of Computer science) (Mercury Learning and Information, 2017)
With numerous examples that the reader can run just as presented, this book is appropriate for both the computer science undergraduate course in 3D graphics programming using OpenGL and for professionals who are interested in mastering 3D graphics skills. --